EFEKTIVITAS PROGRAM DESA MANDIRI SAMPAH DI DESA JUGO KECAMATAN DONOROJO KABUPATEN JEPARA - Bashiroh, Mahida; Maesaroh, Maesaroh; Pupspo Priyadi, Budi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
National waste management is the government's effort to reduce waste generation. Various efforts have been made by the Indonesian government which are followed up by the Regional Government to overcome waste generation in each region. One of the efforts is the Desa Mandiri Sampah Program, this program is an effort to manage waste independently at the village level to achieve a clean and healthy environment. This research uses descriptive qualitative methods with interview techniques, literature studies and documentation. The use of theory to answer research problems is Siagian's theory with aspects of effectiveness with the aim of analyzing the effectiveness of the Desa Mandiri Sampah program in Jugo Village, Donorojo District, Jepara Regency and the inhibiting factors in the implementation of the Desa Mandiri Sampah program. The results showed that the clarity of the objectives to be achieved was understood by the people of Jugo Village, the process of analyzing and determining a stable policy was quite effective because there was a Village Regulation on Waste Management specifically for Jugo Village, and infrastructure facilities were not effective enough and helped in the implementation of the Desa Mandiri Sampah. In contrast, the aspects of the effectiveness of program preparation, clarity of goal achievement, careful planning, effective and efficient task implementation, and supervision have not run optimally. The lack of effectiveness of the Desa Mandiri Sampah program is influenced by inhibiting factors, namely human resources, budget resources and the informal sector of waste management by collectors. Recommendations that can be given are to increase motivation regularly to the community, coordinate wages by distinguishing between other needs and waste management needs, establish communication and remind collectors regularly to be on time.